Variations in the plasticity of functional traits indicate the differential impacts of abiotic and biotic factors on the structure and growth of trees in tropical dry forest fragments - Chaturvedi, Ravi Kant; Pandey, Santosh Kumar; Tripathi, Anshuman; Goparaju, Laxmi; Raghubanshi, Akhilesh Singh; Singh, J. S. (Frontiers in Plant Science, 2024)
Abiotic and biotic factors have considerable impact on plasticity of plant functional traits, which influence forest structure and productivity, however their inter-relationships have not been quantified for fragmented tropical dry forest (TDF) ecosystems. We asked the following questions: (1) what are the variations in plasticity of functional traits due to soil moisture availability in TDF fragments? ( 2) what is the role of soil nutrients and forest disturbances in influencing variations in plasticity of functional traits in the TDF fragments?, and (3) how do the variations in the plasticity of functional traits influence the structure and productivity of TDF fragments? Based on linear mixed effects result, we observed significant variations among tree species for soil moisture content (SMC) under the canopy, and selected functional traits across forest fragments. We categorized tree species across fragments by PCA and HCPC analyses into three functional types, viz., low wood density high deciduous (LWHD), high wood density medium deciduous (HWMD), and high wood density low deciduous (HWLD). Assemblage of functional traits suggested that the LWHD functional type exhibits drought avoiding strategy, whereas HWMD and HWLD adopt drought tolerant strategy. Our study showed that the variations in functional trait plasticity, and structural attributes of trees in three functional types exhibit contrasting affinity with SMC, soil nutrients, and disturbances, although LWHD functional type was comparatively more influenced by soil resources and disturbances, compared to HWMD and HWLD along declining SMC and edge distance, plasticity in functional traits for LWHD functional type exhibited greater variations in traits associated with conservation of water and resources, whereas for HWMD and HWLD, the traits exhibiting greater plasticity were linked with higher productivity and water transport. The cumulative influence of SMC, disturbances and functional trait variations was also visible on relative abundance of functional types in large and small sized fragments. Our analysis further revealed the critical differences in responses of functional trait plasticity of the coexisting tree species in TDF, which suggests that important deciduous endemic species with drought avoiding strategies might be prone to strategic exclusion under expected rise in anthropogenic disturbances, habitat fragmentation and resource limitations.